Effect of green banana pulp powder on microbiological quality of chevon nuggets during refrigerated storage - Shaikh F.R, Sultan; Devangare, A. A.; Raziuddin, Mohammad; Gaikwad, N. Z.; Suryawanshi, R. D.; Awandkar, S. P.; Kulkarni, R. C. (Journal of Meat Science, 2023)
Functional meat products are often created by reformulating meat and adding health promoting ingredients such as fibres, prebiotics, probiotics, polyunsaturated fatty acids and antioxidants. Present research was undertake to study the effect on incorporation of 4% green banana pulp powder on physico-chemical, microbiological and sensory characteristics of chevon nuggets stored at refrigeration temperature (4±1˚C) in low density polyethylene (LDPE) pouches. During storage of product pH, Thiobarbituric acid value and tyrosine values increased significantly (p<0.05). The microbial quality parameters such as total plate count increased throughout the storage period up to 16th days but were within the permissible limits. However, psychrophilic count were not observed at 0 day but increased from 4th day to 16th days of storage. Sensory scores for all sensory characteristics declined progressively with the advancement of storage period of 16th days. Incorporation of 4% green banana pulp powder in chevon nuggets was very much acceptable up to 16th day of refrigerated storage as compared to control.